The Role of Social-Media in Increasing Millennial Political Participation in the Medan Johor Subdistrict - Rocky Arfan; Suryanef Suryanef; Al Rafni (JED (Jurnal Etika Demokrasi), 2023)
Millennials' subordinate role and participation in the political process have resulted in declining trust. Social media is used in several ways during regional elections and other political events, like campaigning for candidates' spouses. The purpose of this study is to analyze the role of social media in increasing the political participation of millennials in the 2021 Medan mayoral election with a case study on the couple Bobby Nasution and Aulia Rachman in Medan Johor District. Four 20-year-old respondents from the Medan Johor District were interviewed for this qualitative study. The data is analyzed descriptively. The results show that social media is an essential part of the political process, including collecting aspirations and public participation among the spouses of regional head candidates. In Medan, Johor, millennials believe that using social media as a catalyst to participate in politics tends to be less effective. The role of social media is indeed able to increase the participation of millennials, but it is not based on reality. The role of social media in the selection of Bobby Nasution and Aulia Rachman's partner is: a) as an agent of political socialization to deliver the program to be carried out; b) for the prestige manikin of the couple Bobby Nasution and Aulia Rachman; c) as a means of online campaigning; d) as a place for the dissemination of information related prospective spouses. Social media is a driver and distributor of the latest information updates from prospective couples to attract public participation and trust, especially among millennials.